2014
DOI: 10.1159/000368337
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G4, Autoimmune Pancreatitis and Pancreatic Cancer

Abstract: Background: Immunoglobulin G4 (IgG4)-related diseases are a group of diseases characterized by enlargement of the affected organs, elevation of serum IgG4, massive infiltration of affected organs with lymphocytes and plasma cells with IgG4 positivity and tissue fibrosis. Type I autoimmune pancreatitis is one form of IgG4-related disease. For IgG4-related diseases, various localizations are described for up to 10% of malignancies. The aim of our study was to examine IgG4 serum levels and pancreatic tissue with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 15 publications
0
13
0
5
Order By: Relevance
“…Serum markers of AIP (notably serum IgG4) are often helpful in diagnosis of both conditions[ 12 ]. However, IgG4 levels exceeding twice the upper limit of normal were found in a considerable proportion of patients with pancreatic cancer and thus this marker cannot be used alone to exclude the diagnosis of malignancy[ 13 ]. In cases where the presence of pancreatic cancer cannot be ruled out with certainty, pancreatic resection is indicated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Serum markers of AIP (notably serum IgG4) are often helpful in diagnosis of both conditions[ 12 ]. However, IgG4 levels exceeding twice the upper limit of normal were found in a considerable proportion of patients with pancreatic cancer and thus this marker cannot be used alone to exclude the diagnosis of malignancy[ 13 ]. In cases where the presence of pancreatic cancer cannot be ruled out with certainty, pancreatic resection is indicated.…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, this represents the largest ever published group of patients with co-occurrence of PC and AIP. Pancreatic cancer in patients with AIP has so far been documented only in individual cases[ 13 , 17 - 20 ]. Recently, two patients with both AIP and PC were described in a study that examined serum IgG4 level in 106 patients with histologically confirmed pancreatic cancer[ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum IgG4 levels alone are unsuitable for distinguishing AIP from pancreatic cancer; serum IgG4 level > 140 mg/dl has a sensitivity of 76 % and specifi city of 93 % in diagnosing of AIP (9). Notably, 5 % of healthy persons and approximately 10 % of the patients with pancreatic cancer have slightly (about 2-fold) elevated IgG4 (9,25,26). Increasing the cutoff to 280 mg/dl decreases sensitivity, but improves specifi city to 99 % in diagnosis of AIP (16).…”
Section: Discussionmentioning
confidence: 99%
“…Аналогично, в случае компрессии желчных протоков следует ожидать увеличения показателей холестаза. В случае подозрения на аутоиммунную природу показано определение IgG и IgG4 [6]. При подозрении на злокачественность следует контролировать уровень CА-19-9.…”
Section: диагностикаunclassified